Práticas de leitura e escrita por meio do gênero digital podcast - Andrade, Elisângela Oliveira (2023)
This research carried out a case study on the discursive genre Podcast as a catalyst for language practices at school in a 9th grade class, since it offers the opportunity for the teacher to work not only with orality that is invisible in Portuguese Language (LP) classes, but also to mobilize and articulate all the axes of these practices. To do so, we used retextualization as a guiding concept for the activities to be developed, which highlighted aspects of the relationship between orality-writing and writing-orality, involving complex operations that interfere with the use of language. In this direction, reflections on practices to improve reading/listening, (re)writing, orality and linguistic/semiotic analysis were indispensable for the exercise of citizenship and the general objective was to develop an educational proposal, Itacast, as a didactic strategy to foster them in Portuguese language classes. We carried out this study in a class of the 9th grade of elementary school, in the afternoon shift, composed of twenty-five (25) students from the state education network of Sergipe in the municipality of Itabaiana, whose school is located in the urban area. As theoretical assumptions, we have Bakhtin (1992) and Marcuschi (2001; 2002; 2008 and 2010) with conceptions about textual genres, textual production, comprehension, orality, writing and Retextualization activities; Oliveira and Valencia (2022) to discuss the digital podcast genre; Macedo (2007) and Araújo (2010) to argue about Portuguese Language Learning Objects; on the principles of multiliteracies and Information and Communication Technologies (ICTs), Rojo (2012 and 2013); among other theorists who contributed to the clarification of the problem. The methodology started from a quantitative and qualitative approach, and the method employed was the case study. As instruments for collecting information, we opted for the production of oral and written texts (podcast scripts) and the performance of a set of reading and writing activities focused on the digital genre chosen for this purpose, which presents the possibilities of interaction , participation and production of the multimodal podcast genre in LP teaching. Finally, the results were achieved with the good development of the student's communicative competence in both oral and written language modalities, contributing to the formation of the reader/text producer and valuing the importance of working on writing and oral communication in Portuguese Language classes, mainly through the production of a journalistic podcast, in a multimodal perspective.